Edukasi Pencegahan Anemia dan Pemeriksaan Kadar Hemoglobin pada Remaja Putri di Kelurahan Gedangan Kecamatan Grogol Kabupaten Sukoharjo - Prabandari, Anggraeni Sih; Novita Sari, Ajeng; Fredericus Pramonodjati; Anastasia Indarwati Utomo; Pradita Yudi Saputro (UNIVERSITAS NGUDI WALUYO, 2023)
Growth spurt, lack of consumption of animal protein sources, consuming tea/coffee along with main meals and menstruation every month can be causes of anaemia in female adolescent. The incidence of anaemia in female adolescent in Sukoharjo Regency is 28.08% and it is predicted that it will continue to increase if preventive measures are not taken, one of which is by education on anaemia prevention. Therefore, hemoglobin (Hb) levels have been checked to determine the status of anaemia in female adolescent in Gedangan Village, Grogol District, Sukoharjo Regency. In addition to measuring Hb levels, education is also carried out in the form of scientific lectures and discussions. The number of participants in this activity was 23 people. Based on the results of Hb measurement, data were obtained as many as 20% suffer from anaemia and 80% are not anaemic. The knowledge level of female adolescent was increased after being educated, with the result that 82.6% had knowledge at a